Petroleum Geochemical Assessment of Shale Samples from Well D, Southern Offshore Niger Delta Basin, Nigeria - Ndip, Edwin Ayuk; Ntoh, Ayuk Enow Clinton; Wotanie, Ligbwah Victor (Anuário do Instituto de Geociências, 2025)
This study evaluates the organic matter richness, hydrocarbon generative potential, and thermal maturity of sediments from Well D, located in the southern offshore Niger Delta Basin, using Total Organic Carbon (TOC) analysis, Rock-Eval pyrolysis, and kerogen classification. The TOC content of the analyzed samples ranges from 1.75 to 6.62 wt.%, with an average of 2.74 wt.%, indicating good to excellent source rock potential. S1 and S2 values, averaging 5.37 mg HC/g rock and 6.91 mg HC/g rock, respectively, further highlight the organic richness and hydrocarbon potential of these sediments. The S1/TOC ratio (average 1.97) suggests significant free oil presence and active hydrocarbon expulsion. Kerogen classification, based on a modified Van Krevelen diagram and Hydrogen Index (HI) versus Tmax plots, reveals predominantly Type II kerogen (oil-prone) with a minor mix of Type II/III (oil and gas-prone). Approximately 91% of the samples exhibit sufficient thermal maturity to generate hydrocarbons, while 9% remain immature. Genetic potential values ranging from 6.16 to 31.06 mg HC/g rock underscore the significant hydrocarbon potential of key intervals, especially those within the optimal oil window. The findings confirm that Well D sediments possess substantial potential for hydrocarbon generation, driven by favorable TOC levels, kerogen quality, and thermal maturity. These results align with previous studies of Niger Delta source rocks, providing valuable insights for future exploration and development in the region.